Penolakan Gugatan Waris Dalam Putusan Hakim Pengadilan Agama Ditinjau Dari Segi Hukum Acara Peradilan Agama - Dian Alfin Nur (JoEMS (Journal of Education and Management Studies), 2020)
The rejection of the inheritance suit by the Panel of Judges that occurred in the Jombang Religious Court was because some of the plaintiffs had withdrawn their claims which caused a formal flawed suit (plurium litis consortium) that is, not all heirs participate as parties to the case. The purpose of this research is to find out the reasons why judges do not accept inheritance lawsuits and analyze them in terms of civil procedural procedural law for religious courts. This research is a qualitative research. The results of the ongoing research show that the basis used by the panel of judges is not appropriate because the core contained in the basis used by the panel of judges is different from the case in the Jombang Religious Court